Unexpected limited chronic dissection of the ascending aorta - Venturini, Andrea (BioMed Central, 2008)
We report a rare case of a limited chronic dissection of the ascending aorta that was accidentally discovered at operation performed for severe aortic stenosis and moderate to severe dilatation of the ascending aorta. Preoperative investigations such as transoesophageal echocardiography and cardiac catheterization missed the diagnosis of dissection. Intraoperative findings included a 3.5 cm eccentric bulge of the ascending aorta and a 5 mm circular shaped intimal tear comunicating with a limited hematoma or small dissection of the media layer. (The rarety of the report is that the chronic dissection is limited to a small area (approximatively 3.5 × 2.5 cm) of the ascending aorta).